Pengembangan Modul Sistem Pencernaan Makanan Berbasis Literasi Sains Kelas VIII MTsN Padang Japaang - Delfita, Rina; Haviz, Muhammad; Nurhasnah, Nurhasnah; Ulva, Rifka Khaira (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This research is based on low scientific literacy of students. This is due to many factors, one of which is the textbook used less able to develop the scientific literacy students. Educators are required to provide teaching materials like a module that develops scientific literacy students. This type of research is Research and Development (R & D) model 4-D models by Thiagarajan and Sammel. Instruments used are questionnaire validity and questionnaire of practicality. The result show that the characteristics of prototype are the knowledge of science, the investigative nature of science, science as a way of thinking, interaction of science and technology, and society (scientific literacy contents). At process of design, a module of digestive system based scientific literacy develop based on the as reality and good practical education. Module have been categorized as valid based on expert judgment. The learning module have been categorized as practical based on the observation, respons es of teachers and learners. In conclusion, developing a module of digestive system based scientific literacy have the relevancy and internal consistency to develop scientific literacy students.